A Weevil, Eurhinus magnificus Gyllenhal (Insecta: Coleoptera: Curculionidae) - Bryan J. Ulmer; Rita E. Duncan; Jens Prena; Jorge E. Peña (EDIS, 2007)
EENY-417, a 6-page illustrated fact sheet by Bryan J. Ulmer, Rita E. Duncan, Jens Prena, and Jorge E. Pena, is part of the Featured Creatures collection. It describes this brilliantly colored imported potential grape pest that has been found in Broward and Miami-Dade counties, its synonymy, distribution, description, biology, host plants and damage, and management. Includes selected references. Published by the UF Department of Entomology and Nematology, September 2007.